Degradação eletroquímica do antibiótico ciprofloxacina utilizando eletrodos de diamante dopado com boro e dióxido de chumbo - Wächter, Naihara (2014)
Initial potentials for the oxygen evolution reaction (OER) of 2.23, 2.30, 2.36, and ~1.55 V vs. Ag/AgCl (3 mol L 1 KCl) were obtained by linear sweep voltammetry (LSV) in 0.1 mol L 1 Na2SO4 for the 2500, 100, and 500 ppm BDD, and the Ti-Pt/β-PbO2 electrodes, respectively. When LSW was used in the presence of 200 mg L 1 ciprofloxacin hydrochloride (Cl-cipro) in 0.1 mol L 1 Na2SO4, an oxidation peak was observed before the occurrence of the OER, for all the electrodes. Using the 100 ppm BDD electrode, LSV experiments were carried out for different Cl-cipro concentrations in 0.1 mol L 1 Na2SO4, which confirmed the nature of the oxidation peak at ~1.5 V vs. Ag/AgCl (3 mol L 1 KCl). With this electrode, LSW experiments were also carried out at different sweep values using the previously mentioned Clcipro solution, with results that indicated that the oxidation of the pharmaceutical drug is mainly a diffusion-controlled process. For the electrochemical degradation of ciprofloxacin (50 mg L 1 Cl-cipro) in 0.1 mol L 1 Na2SO4, using the BDD and Ti-Pt/β- PbO2 electrodes in filter-press type reactors, the effect of pH, flow rate, temperature, and current density was investigated. The degradation process was favored when the electrolyses were carried out at pH 10, which is related to the pKa values of the molecule. Yet the flow rate presented different effects; for the Ti-Pt/β-PbO2 electrode, the process efficiency was improved for a high value (6.5 L min 1), contrary to what was observed for the BDD electrodes (2,5 L min 1). The influence of temperature on the process was little marked, having a significant effect only for the 2500 ppm BDD electrode (best results at 10 °C). On the other hand, the electrodegradation of ciprofloxacin occurred faster at higher current densities, since greater amounts of the oxidizing agents are formed under these conditions. For the optimized condition, the 100 ppm BDD electrode presented the best performance in the oxidation and mineralization of the pharmaceutical drug. Under that condition and using the 100 ppm BDD, five ciprofloxacin degradation intermediates were identified (m/z 263, 306, 334, 348, and 362), which led to the proposal of an initial degradation route for its electrooxidation.